Marketing digital en Ímpetu Gym de la ciudad de Babahoyo periodo 2021. - Echeverria Carrasco, Juan Carlos (2022)
This end-of-grade research aims to identify a digital marketing plan mentioning the most important aspects to take into account to ensure that the impetus gym captures clients that positions the business in the market, the absence of digital media was identified to carry out marketing and little knowledge of digital content as a central problem, therefore, through theoretical references, I inquired about digital marketing and the benefits that it causes in the gym, taking a descriptive methodology and observation techniques and the survey through the instrument I feel this is a questionnaire of questions that put the gym in evidence, concluding that it needs a digital marketing strategy based on social networks.